Indigenous peoples versus the state FPIC and resource extraction in the Cordillera Region, Philippines - Peñalba, Maileenita A. (2016)
The discourse on indigeneity has been primarily framed within the context of identity politics, on the notion that being indigenous has a political meaning that needs articulation, recognition and representation. Indigeneity is also a matter of positioning. Given this, the political identity of the indigenous peoples is said to be forged in situations of strife and resistance. The indigenous peoples in the Philippines, commonly branded as among the "marginalized", however, have found ways to strengthen their position within the decision-making arenas set-up by the state such as the Free and Prior Informed Consent (FPIC) process. This paper explores the 'uneasy' relationship between the indigenous peoples and the state when resource extraction is concerned. It particularly unpacks the power relations between the state, which strongly promoted mining during the administration of President Gloria Macapagal-Arroyo and the indigenous peoples whose resource-rich lands have become the primary target of an aggressive mining industry. The indigenous peoples' positioning on the issue of mining in the Cordillera Region, Philippines will be discussed along with the counter position of the state in order to illustrate how identity politics plays a crucial role in resource access, use and management in the region. The study adopts critical discourse analysis, which provides the lens that facilitates the discovery of possible convergence between the state and the indigenous peoples' rendering of concepts like FPIC and resource extraction, so that a peaceful and productive engagement between these two contending parties may be established.
Keywords: Indigenous peoples; Cordillera region; Natural resources; Resource exploitation